Temporal dynamics of acoustic diversity in managed forests - Müller, Sandra; Jahn, Olaf; Jung, Kirsten; Mitesser, Oliver; Ammer, Christian; Böhm, Stefan; Ehbrecht, Martin; Farina, Almo; Renner, Swen C.; Pieretti, Nadia; Schall, Peter; Tschapka, Marco; et al. (Frontiers in Ecology and Evolution, 2024)
IntroductionIn production forests, management can have cascading effects on biodiversity and ecosystem services. Acoustic diversity reflects the diversity of vocalizing animals and has also considerable recreational value for human well-being, but the relationship between acoustic diversity and forest management remains largely unexploredMethodWe recorded acoustic diversity on forest plots along a gradient of silvicultural management intensity (SMI) in three regions of Germany. We explored the diurnal and seasonal temporal dynamics in acoustic diversity index (ADI) from March to July using generalized additive mixed models (GAMMs). We further investigated the interrelation between acoustic diversity and silvicultural management intensity, forest structural diversity, as well as tree diversity, bird species richness and abundance using structural equation modeling (SEM).ResultsSilvicultural management intensity had significant effects on the temporal dynamics of ADI in May and June from dawn till dusk, but variance explained by SMI was low. We confirmed our hypothesis that ADI was reduced by SMI due to its cascading effects on forest structural diversity and bird species richness and abundance.DiscussionAcoustic diversity indices can provide valuable insights into how forest management affects the acoustic activity of soniferous communities. We discuss how this can indicate both changes in species diversity as well as their vocal activity. We further address potential implications for forest management.